An Analysis of Types and Forms of Code-Mixing by Deddy Corbuzier and Faiz Rahman on Youtube Channel Deddy Corbuzier - Cika Nurviatri; Widya Fhitri; Irsyad Shabri; Rahma Yanti; Yalmiadi (Jurnal Ilmiah Langue and Parole, 2023)
The aim of this study to find out types and forms code mxing used in Deddy Corbuzier's YouTube Channel video " Kenapa Baru Kita Ceritakan… KRI Nanggala 402-Faiz Rahman". " In conducting the analysis, the results obtained with the research method used is a qualitative descriptive method. In collecting the data this research used heed method, this method followed by the simak bebas libat cakap technique and the analysis method used the Agih method and followed by Bagi Unsur Langsung technique. After doing the analysis, it was found that 51 data were found in the video. As a result, 51 data with the types of Outer Code-Mixing is dominant with a percentage of 100%, while in the inner no data is found. In the forms, there are 21 data on words, 17 data on phrases, 3 data on hybrids, 1 data on repetition words, 2 on idioms, and 11 data on clauses.